A new handover authentication protocol based on bilinear pairing functions for wireless networks. (1st January 2015) - He, Debiao; Khan, Muhammad Khurram; Kumar, Neeraj
Seamless handover over multiple access points is highly desirable to mobile nodes, but ensuring security and efficiency of this process is challenging. Many such protocols have been proposed but most of them are either insecure or inefficient. Very recently, He et al. proposed an improved protocol to overcome the weakness of a novel handover authentication protocol, namely PairHand. Later, they pointed out that their protocol is vulnerable to a private key compromised problem under certain circumstances and proposed an improved protocol to overcome the weakness. In this paper, we examine the security of He et al.'s improved protocol and show it is vulnerable to a private key compromised problem. To improve security, we propose a new ID–based signature protocol and construct a new handover authentication protocol based on the proposed signature protocol.